2019
DOI: 10.1016/j.jaci.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate ameliorates allergic airway inflammation by limiting eosinophil trafficking and survival

Abstract: Background: Lung eosinophilia is a hallmark of asthma, and eosinophils are believed to play a crucial role in the pathogenesis of allergic inflammatory diseases. Short-chain fatty acids (SCFAs), such as acetate, propionate, and butyrate, are produced in high amounts in the gastrointestinal tract by commensal bacteria and can be absorbed into the bloodstream. Although there is recent evidence that SCFAs are beneficial in allergic asthma models, the effect on eosinophils has remained elusive. Objective: The role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 58 publications
4
124
0
5
Order By: Relevance
“…Recent studies have reported that SCFAs may reduce allergic airway inflammation by limiting eosinophil trafficking and survival. 6,7 The present study demonstrated that clostridiales was significantly elevated in allergic mice after azithromycin treatment, so we assessed alterations in the fecal levels of SCFAs. The propionate level was significantly decreased in the cefixime group (not in the azithromycin group) compared with the OVA-treated group; the acetate level was higher in the azithromycin group than in the OVA-treated group.…”
Section: Altered Gut Microbiota By Azithromycin Attenuates Airway Infmentioning
confidence: 99%
“…Recent studies have reported that SCFAs may reduce allergic airway inflammation by limiting eosinophil trafficking and survival. 6,7 The present study demonstrated that clostridiales was significantly elevated in allergic mice after azithromycin treatment, so we assessed alterations in the fecal levels of SCFAs. The propionate level was significantly decreased in the cefixime group (not in the azithromycin group) compared with the OVA-treated group; the acetate level was higher in the azithromycin group than in the OVA-treated group.…”
Section: Altered Gut Microbiota By Azithromycin Attenuates Airway Infmentioning
confidence: 99%
“…Notably, HDAC inhibition requires millimolar concentrations of SCFA usually seen in the colon (vs micromolar lung SCFA levels). Additionally, FFAR2-independent effects of SCFAs have been reported in lung eosinophils and mast cells in asthma and allergic airway disease (16,49).…”
Section: Discussionmentioning
confidence: 99%
“…Other models of allergic airways disease have reported reduced eosinophilic-mediated type 2 inflammation in mice injected with butyrate [89]. In human eosinophils, SCFA attenuated migration, adhesion and survival via GPCR independent mechanisms accompanied by increased histone acetylation [89].…”
Section: Scfa Effects On Innate Immune Functionmentioning
confidence: 97%